Assessment of coagulase-negative staphylococci isolated from blood cultures of patients with leukemia in the period 2009-2011 - Roberta Filipini Rampelotto; Rosiéli Martini; Rosmari Horner; Silvana Oliveira Santos (São Paulo State University (UNESP), 2016)
Leukemic patients have high probability of developing bacteremia, especially due to the impairment of their immune system and as a consequence of chemotherapy. These infections have been growing significantly in different regions, particularly in university hospitals and are responsible for high rates of morbidity and mortality. We evaluated coagulase-negative staphylococci (CoNS) isolated from blood cultures from patients with leukemia. A retrospective study of blood cultures in the period from 2009 to 2011 was conducted at the University Hospital of Santa Maria. In the period of this study was possible to analyze 282 positive blood cultures, being 46.45% (131/282) caused by CoNS. Staphylococcus epidermidis was the prevalent specie. Regarding the hospitalization sectors of patients, the Treatment Center for Children with Cancer showed the highest prevalence, 67.37%. The isolates were predominant in males and in the age group between 0-22 years old. In this study the CoNS represented the most isolated microorganisms. The resistance presented by these microorganisms is a concern since it limits the treatment for bloodstream infections in these patients with compromised immune system. Retrospective studies of prevalence provide us with results for the local epidemiology to be known, considered essential for the antimicrobial treatment, especially when referring to patients with a weakened immune system and admitted in university hospitals. Keywords: Bacteria. Blood. Staphylococcus. Leukemia.   RESUMO Avaliação de Staphylococcus coagulase negativo isolados de hemoculturas de pacientes com leucemia no período compreendido entre 2009 a 2011 Pacientes leucêmicos possuem grande probabilidade de desenvolver bacteremia, especialmente devido ao acometimento de seu sistema imune e como consequência da quimioterapia. Esse tipo de infecção vem aumentando significativamente em diferentes regiões, principalmente nos hospitais universitários, e são responsáveis por altas taxas de morbidade e mortalidade. Foram avaliados Staphylococcus coagulase negativos isolados de culturas de sangue de pacientes com leucemia. Realizou-se a avaliação de Staphylococcus coagulase negativo (SCoN) isolados de hemoculturas de pacientes com leucemia. Efetuou-se um estudo retrospectivo das hemoculturas realizadas no período de 2009 a 2011 no Hospital Universitário de Santa Maria. No período deste estudo foi possível analisar 282 hemoculturas positivas, sendo 46,45% (131/282) causadas por SCoN. Staphylococcus epidermidis foi a espécie prevalente. Em relação aos setores de internação dos pacientes, o Centro de Tratamento da Criança com Câncer mostrou a maior prevalência, 67,37%. Os isolamentos predominaram em pacientes do sexo masculino e na faixa etária compreendida entre 0 a 22 anos. Neste estudo os SCoN representaram os microrganismos mais isolados. A resistência apresentada por estes microrganismos constitui preocupação, uma vez que limita as opções de tratamento por infecções de corrente sanguínea neste tipo de pacientes com o sistema imune comprometido. Estudos retrospectivos de prevalência nos fornecem resultados para que seja conhecida a epidemiologia local, considerada essencial para o tratamento antimicrobiano, principalmente quando se refere aos pacientes com o sistema imune debilitado e internados em hospitais universitários. Palavras-chave: Bactérias. Sangue. Staphylococcus. Leucemia.